Pengaruh Manajemen Inovasi dan Kinerja Rantai Pasok terhadap Pengembangan UMKM Tekstil - Nurhidayah, Rika; Muliansyah, Dadah; Azis, Nur; Adham, Ibnu; Wibowo, Bimo Teguh; Alvianita, Syavilla; Reskiyah, Efri; Nabila, Tiara; Salsabila, Tiara (JURNAL EKONOMI, BISNIS DAN HUMANIORA, 2024)
This study analyzes the impact of innovation management and supply chain performance on the development of textile MSMEs in Banten Province. The increasingly intense competition following the COVID-19 pandemic demands MSME actors to innovate and manage their supply chains efficiently to enhance competitiveness and business sustainability. The study also explores the synergy between these two variables. Adopting a quantitative approach with a survey method, data were collected from 180 respondents, consisting of textile MSME owners or managers. The research instrument, a structured questionnaire, was analyzed using multiple regression to examine the effects of the variables. The findings reveal that innovation management has a significant positive effect on MSME development (β=0.45; p=0.000). Factors such as product innovation frequency, technology adoption, and employee training significantly contribute to business growth. Supply chain performance also demonstrates a significant impact (β=0.38; p=0.002), with raw material procurement efficiency, distribution speed, and supplier relationships identified as key factors. Notably, the interaction between innovation management and supply chain performance exerts an even greater influence (β=0.60; p=0.000), underscoring the critical importance of synergy between these aspects. These findings align with Schumpeter's (1934) innovation theory and Christopher's (2016) supply chain theory, while also corroborating prior studies, such as Tidd and Bessant (2020), which emphasize the role of innovation in enhancing MSME competitiveness. This research provides a novel contribution by highlighting the importance of integrating innovation and supply chain efficiency in the context of Indonesian textile MSMEs. Future studies are recommended to expand geographic scope, explore other sectors, and adopt mixed-method approaches to deepen the understanding of these dynamics.